Impact of mTOR gene polymorphisms and gene-tea interaction on susceptibility to tuberculosis - Wang, Mian (World J Clin Cases, 2020)
BACKGROUND: mTOR gene is a key component of the PI3K/Akt/mTOR signaling pathway, and its dysregulation is associated with various diseases. Several studies have demonstrated that tea drinking is a protective factor against tuberculosis (TB). This study was designed to explore five single nucleotide polymorphisms (SNPs) of mTOR in the Han population of China to determine how their interactions with tea drinking affect susceptibility to TB. AIM: To investigate if the polymorphisms of mTOR gene and the gene-tea interaction are associated with susceptibility to TB. METHODS: In this case-control study, 503 patients with TB and 494 healthy controls were enrolled by a stratified sampling method. The cases were newly registered TB patients from the county-level centers for disease control and prevention, and the healthy controls were permanent residents from Xin’ansi Community, Changsha city. Demographic data and environmental exposure information including tea drinking were obtained from the study participants. We genotyped five potentially functional SNP sites (rs2295080, rs2024627, rs1057079, rs12137958, and rs7525957) of mTOR gene and assessed their associations with the risk of TB using logistic regression analysis, and marginal structural linear odds models were used to estimate the gene-environment interactions. RESULTS: The frequencies of four SNPs (rs2295080, rs2024627, rs1057079, and rs7525957) were found to be associated with susceptibility to TB (P < 0.05). Genotypes GT (OR 1.334), GG (OR 2.224), and GT + GG (OR 1.403) at rs2295080; genotypes CT (OR 1.562) and CT + TT (OR 1.578) at rs2024627, genotypes CT (OR 1.597), CC (OR 2.858), and CT + CC (OR 1.682) at rs1057079; and genotypes CT (OR 1.559) and CT + CC (OR 1.568) at rs7525957 of mTOR gene were significantly more prevalent in TB patients than in healthy controls. The relative excess risk of interaction between the four SNPs (rs2295080, rs2024627, rs1057079, and rs7525957) of mTOR genes and tea drinking were found to be -1.5187 (95%CI: -1.9826, -1.0547, P < 0.05), -1.8270 (95%CI: -2.3587, -1.2952, P < 0.05), -2.3246 (95%CI: -2.9417, -1.7076, P < 0.05) and -0.4235 (95%CI: -0.7756, -0.0714, P < 0.05), respectively, which suggest negative interactions. CONCLUSION: The polymorphisms of mTOR (rs2295080, rs2024627, rs1057079, and rs7525957) are associated with susceptibility to TB, and there is a negative interaction between each of the four SNPs and tea drinking.